(untitled) (The Pakistan Development Review, 1994)
The emphasis on rural employment generation as a means of poverty alleviation has brought about an increasing focus on the promotion of agribusiness and rural enterprises during the last few years. The concern about the distribution of the benefits of economic growth has further heightened its importance. The debate, which centred on the apparent trade-off between economic growth on the one hand and social equity on the other, was fuelled by the apparent "urban bias" of the strategies adopted in a majority of developing countries, and by the fact that poverty tended to be concentrated in the rural areas. The book under review, which the author terms in the "Preface" as a "manual", "is designed primarily for planners, public administrators, and project personnel in countries or international agencies implementing or considering a development strategy in which agribusiness and rural enterprise projects are viewed as desirable as a policy instrument for generating employment and income". The underlying premise is that a diverse and scattered but overwhelming evidence exists here of labour-intensive, small-scale, and relatively efficient enterprise system, the expansion of which would have a favourable impact on the employment and incomes of the rural landless and poor and provide beneficial linkages to the small-farm sector. There is a need, therefore, to distil from this evidence the lessons in project identification and design and implementation in order to achieve both growth and equity at the same time.